Impact of leptin or melatonin on Sema4D overexpression-related bone metabolism - Zhenen Lin; Shengren Xiong; Yu Lin; Zhaohui Li; Dan Xie; Xuchao Lin; Xuesheng Chen; Xueyi Lin (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Purpose The current study aims to investigate the regulatory impact of leptin or melatonin on bone metabolism as well as the underlying mechanism in conjunction with Sema4D (monoclonal antibody to semaphorin 4D). Methods Rats were used to create the osteoporosis model utilizing the OVX (OVariectomize) technique. Rat tibial specimens from each side were collected for three-dimensional reconstruction and Micro-CT scanning examination. The Hematoxylin-osinstaining (HE) staining technique was used to determine the pathological condition of bone tissues. The ELISA (Enzyme-Linked Immunosorbent Assay) assay was used to measure the amount of estradiol present in the serum. In the current study, there were six groups: control, OVX, OVX + NL (no load group), OVX + Sema4D, OVX + Sema4D + leptin, and OVX + Sema4D + MT (melatonin). Rats were given injections of the Sema4D or leptin overexpressing vectors via the tail vein in accordance with the aforementioned classification. By using a high-resolution micro-CT technology, 3D bone structure was discovered. The activity of tartrate-resistant acid phosphatase-5b (TRAP-5b) and bone-derived alkaline phosphatase (BALP) in serum was assessed using an ELISA. The number of osteoclasts in the metaphysis of the upper tibia was determined using TRAP (tartrate-resistant acid phosphatase) staining. Immunohistochemistry was used to find leptin and bone morphogenetic protein-2 (BMP-2) expressions in bone tissue. Results The BV/TV (Bone volume/Tissue volume), Tb.N (Trabecular number), BMD (Bone Mineral Density), and BMC (Bone Mineral Content) levels were significantly higher in the OVX + Sema4D + leptin and OVX + Sema4D + MT groups compared to OVX + NL, while Tb.Sp (Trabecular separation) levels were significantly lower. In contrast to the OVX group, the bone trabeculae in the OVX + Sema4D + leptin and OVX + Sema4D + MT groups had a relatively complete structure and tended to be organized closely. The amount of bone trabeculae grew drastically, whereas the proportion of TRAP-positive osteoclasts declined dramatically. BMP-2 and leptin were also elevated, while BALP and TRAP-5b activity was reduced. Conclusion Leptin or melatonin improved Sema4d's role in trabecular bone microstructure, bone production, and repairment of trabecular bone loss in osteoporosis rats.